Seven years of advanced energy action: 2013 2019 state legislation in review - Crew, Seth, author; Eisenbeis, Ellen, author; Hoffer, Trina, author; Kelly, Liam, author; Oonk, David, author; Petrella, Carlyn, author; Plant, Tom, author; Tegen, Suzanne, author; Center for the New Energy Economy, publisher (Colorado State University. Libraries, 2020)
States have taken the lead in developing the climate and energy policies that drive clean energy adoption. The period between 2013 and 2019 was characterized by shifts in public opinion concerning energy and climate, dramatic changes in energy markets, and technological innovation. Managing energy supply and demand has become more complex, and as technological progress accelerates, state legislatures have been empowered to lay the policy groundwork to transform energy markets. State responses anticipating and reacting to systemic changes have varied widely. There is no one-size-fits-all approach for advancing a clean energy economy. There are a multitude of policy tools to facilitate transitions in states with diverse economies, political dynamics, and social values. For these reasons, tracking state legislative activity is important for understanding the direction of U.S. energy policy. Using AEL Tracker data, this report looks back at the 3,542 energy-related bills enacted by state policymakers between 2013 and 2019. Throughout this report, we identify notable trends and new policy developments.
Keywords: Energy policy; Renewable energy sources -- Law and legislation; energy markets; state legislation; Advanced Energy Legislation Tracker